Вплив технологічної бази на підвищення рівня виробничих ресурсів сервісного підприємства - Дашивець, Галина Іванівна; Бондар, Андрій Миколайович; В’юник, Ольга Володимирівна; Dashyvets, Halyna; Bondar, Andrii; Viunyk, Olha (Запоріжжя : ТДАТУ, 2022)
UA: Основна мета роботи – виявлення і дослідження комплексних та одиничних показників технологічної бази сервісного підприємства, які впливають на потенціальний рівень технології. Забезпеченість та якість технологічної бази обумовлюється забезпеченістю ремонтно-технологічним обладнанням, оснасткою та пристосуваннями, контрольно-вимірювальними інструментами, запасними частинами і матеріалами. Робочою групою експертів була розроблена анкета з оцінки впливу технологічних факторів на якість послуг. Введені одиничні показники та п’ять ступенів можливих їх значень. Виконано ранжування показників, за результатами експертної оцінки побудовані діаграми коефіцієнтів вагомості для одиничних факторів технологічної бази. Розглянуті фактори дозволили сформулювати основні напрямки підвищення якості ремонту. EN: The main purpose of the work is to identify and study the complex and single indicators of the technological base of the service enterprise, which affect the potential level of technology. The quality of work at service enterprises can be low due to deviations in technological discipline, as a result of "simplification" of technological operations by performers, insufficient quantity and poor quality of spare parts and materials, low accuracy and insufficiency of repair and technological equipment, tooling, devices, tools. In the article, the "tree of goals" was used to analyze the processes of the technical service enterprise and develop an action plan to improve the efficiency of its activities. The level of production resources, on which the quality of repair of products depends, consists of the following complex factors: provision and quality of technological base, coverage and quality of engineering training of production, level of labor force. In turn, these complex factors consist of single factors. Availability and quality of the technological base is determined by the availability of repair and technological equipment, tooling and fixtures, control and measuring tools, spare parts and materials. The working group of experts developed a questionnaire to assess the impact of technological factors on the quality of services. Single indicators and five degrees of their possible values were introduced. The ranking of indicators was performed, according to the results of the expert evaluation, diagrams of weighting coefficients for single factors of the technological base were built. Among the indicators of production availability of repair and technological equipment, the most significant was the indicator of equipment availability; among the indicators of production availability of tooling and fixtures - the indicator of their service quality; among the indicators of production availability of control and measuring tools - the indicator of their availability; among the indicators of production availability of spare parts and materials - the indicator of their quality. The considered factors allowed to formulate the main directions of improvement of repair quality.
The impact of the technological base on increasing the level of production resources of the service enterprise
Дашивець Г. І., Бондар А. М., В’юник О. В. Вплив технологічної бази на підвищення рівня виробничих ресурсів сервісного підприємства. Науковий вісник Таврійського державного агротехнологічного університету : електронне наукове фахове видання. Запоріжжя : ТДАТУ, 2022. Вип. 12. том 3. C. 92-101.
Keywords: якість сервісних послуг; виробничі ресурси; експертна оцінка; коефіцієнт вагомості; діаграма; технологічна база; quality of services; production resources; expert assessment; weighting factor; diagram; technological base